Is it advisable for Asians to drink milk, especially those at risk of osteoporosis? - Jiao, Hao-tian; Yue, Yu-Shan; Yuan, Shuai; Zhou, Xiao-jie; Li, Chong (Frontiers in Nutrition, 2025)
Osteoporosis poses a significant health challenge globally, with particularly high rates anticipated in the Asian region in the forthcoming years. This region has been identified as a potential hotspot for increasing incidences of osteoporosis. Unfortunately, the Asian population has a low consumption of milk and dairy products, which may exacerbate this situation. A deficiency of calcium ions and inadequate consumption of milk and other dairy products significantly exacerbate the risk of developing osteoporosis. Milk, which is a rich source of protein, vitamin D, and various essential minerals, stands out as an optimal dietary choice for managing and potentially mitigating osteoporosis in individuals of Asian descent. Consuming milk provides these vital nutrients while playing a crucial role in maintaining bone health and preventing the loss of bone density. Here, we delve into the multiple nutritional benefits of milk for individuals susceptible to osteoporosis, and discuss comprehensive strategies to overcome challenges that are prevalent within the Asian demographic, such as milk allergies and lactose intolerance.